Baked Clay Animal Figurines of the Karaz Culture from Early Excavations in the Erzurum Archeological Museum - Rabia Akarsu; Elif Şener (Art-Sanat)
Figurines are significant archeological artifacts that depict humans and animals, often serving practical or symbolic purposes. Considering their location, these small artifacts provide significant insights into the belief systems of the cultures to which they belong. The Karaz culture, which flourished between approximately 3500 and 1500 BCE and extended from the Caucasus to the Levant and from Northwestern Iran to Central Anatolia, has been widely studied through the use of ceramic materials, yet there is limited information about its belief system. Besides, studies focusing on figurines from the Karaz culture are scarce. Hence, this study examines 20 baked clay animal figurines housed in the Erzurum Archeological Museum. These artifacts were recovered during early excavations at Pulur Höyüğü (1960), Güzelova Höyüğü (1961), and Sos Höyük (1994–2000) in Erzurum Province, a key center of the Karaz culture. No figurines were discovered at Karaz Höyüğü, the site that gave the culture its name. Within the scope of this article, the figurines were classified typologically, accompanied by detailed descriptions of their forms. Additionally, comparisons were made with similar figurines found in other regions associated with the Karaz culture.